The Impact of Deforestation on Wildlife and Forest Ecosystems - Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
Deforestation, the large-scale removal of forest cover, poses a critical threat to biodiversity and the stability of forest ecosystems. This research examines the multifaceted impact of deforestation on wildlife populations and the ecological integrity of forest environments. By analyzing data from satellite imagery, biodiversity surveys, and case studies from tropical regions such as the Amazon, Congo Basin, and Southeast Asia, this study highlights the direct and indirect consequences of forest loss. The findings reveal that deforestation leads to significant habitat fragmentation, species displacement, and increased vulnerability to extinction, particularly for endemic and specialist species. Additionally, ecosystem services such as carbon storage, water regulation, and soil conservation are severely compromised. The study underscores the urgency of implementing sustainable forest management practices, enforcing anti-logging regulations, and promoting reforestation initiatives to mitigate the adverse effects of deforestation. This research contributes to the global discourse on environmental conservation by emphasizing the intricate connection between forest health and biodiversity preservation.